Psycho-physiological characteristics of students-powerlifters of different training experience, who have affections of muscular skeletal apparatus - V.S. Lobko (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: study of many years' power lifting trainings influence on psycho-physiological and other characteristics of students, who have affections of muscular skeletal apparatus. Material: the research covered 73 students of 18-22 yrs. Age, who have different training experience. To exclude influence of previous training on experiment's results, researches were conducted after 2-3 days of rest. The author studied personality's features (by T. Elers). Psychological diagnostic was conducted by methodic of M.V. Makarenko. Results: different psycho-physiological characteristics, indicators of psychological state and personality's features were found in students, depending on their power lifting training experience. Improvement of functional and nervous power indicators under influence of systemic power lifting trainings was detected. Conclusions: it was determined that improvement of students' sportsmanship is accompanied by noticeable improvement of practically all tested indicators.